The impact of retirement on body mass index in China: An empirical study based on regression discontinuity design - Bin Yuan; Wei Liu; Yuhu Cui (Elsevier, 2023)
An aging population is an important trend of social development, and it will be China's basic national condition for a long time. However, the pressure on domestic pension payments and economic operations will increase daily. The delayed retirement policy is gradually implemented as a critical initiative to improve capital and labor force allocation. The impact of retirement on residents' Body Mass Index (BMI) and weight has become a focus issue. This paper investigates the mechanism of the impact of retirement on residents' BMI using microdata from the China Family Panel Studies (CFPS) 2018, combined with a fuzzy regression discontinuity design to measure the potential health impact of China's current retirement policy on residents. The study finds that: (1) Retirement has a significant negative effect on BMI for women, with retirement leading to a significantly increased risk of deviation from normal BMI levels and significantly increasing the weight of retired women. However, retirement does not have a significant effect on men. (2) Retirement policies affect residents' BMI to different degrees depending on their family size, with the negative effect on women being more pronounced in smaller family sizes. (3) Female residents who retire to help their children with intergenerational care are more likely to maintain normal BMI levels, significantly positively affecting their potential health. (4) Retirement negatively affects BMI through channels such as significantly reducing exercise frequency among female residents. The study demonstrates that retirement policy impacts the BMI and weight of female residents, so the formulation and implementation of delayed retirement policy should be flexible, and family factors such as family sizes and intergenerational care should be considered appropriately.